2010
DOI: 10.1021/jp106949v
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Cluster/Shell Fe3O4/Au Nanoparticles and Application in Protein Detection via a SERS Method

Abstract: We have successfully synthesized cluster/shell Fe 3 O 4 /Au nanoparticles using a pH-sensitive polyethyleneimine (PEI) linker. We propose that PEI binds gold seeds, prevents the formation of large aggregates, and changes the spatial structure in an alkaline environment to bundle several Fe 3 O 4 /Au seed nanoparticles together through a bridging flocculation function, thereby producing cluster/shell Fe 3 O 4 /Au nanoparticles. We successfully applied the synthesized cluster/shell Fe 3 O 4 /Au nanoparticles to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 36 publications
1
74
0
Order By: Relevance
“…3,4 In contrast to the literature, the Fe 3 O 4 @Au composite MNPs in this present study had broader absorption spectra and redshifted maximum absorption wavelength. 3,38,39 Such a redshift phenomenon of the plasmon absorption can be understood in terms of plasmon hybridization with the gold shell layer growth. In addition, because the gold shell layer outside the Fe 3 O 4 core forms a rough surface after a coating of three iterations, strong interaction and coupling of the surface plasmon exists between neighboring nanoparticles, which may also contribute to the plasmon resonance redshift.…”
Section: Effect Of Fe 3 O 4 @Au Composite Mnps On the Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In contrast to the literature, the Fe 3 O 4 @Au composite MNPs in this present study had broader absorption spectra and redshifted maximum absorption wavelength. 3,38,39 Such a redshift phenomenon of the plasmon absorption can be understood in terms of plasmon hybridization with the gold shell layer growth. In addition, because the gold shell layer outside the Fe 3 O 4 core forms a rough surface after a coating of three iterations, strong interaction and coupling of the surface plasmon exists between neighboring nanoparticles, which may also contribute to the plasmon resonance redshift.…”
Section: Effect Of Fe 3 O 4 @Au Composite Mnps On the Organsmentioning
confidence: 99%
“…0.05). 39,40 In addition, the detection of effective surface charge showed that the zeta potential of Fe 3 O 4 -MNPs was close to neutral charge (-3.6 ± 1.8 mV) at pH 7.4, the presence of gold shell shifted the zeta potential value to -23.2 ± 1.8 mV. A slightly high negative zeta potential imparted by Fe 3 O 4 @Au composite MNPs compared with Fe 3 O 4 -MNPs confirms an amount of gold coverage on the magnetite surface, which was in agreement with the literature.…”
Section: Effect Of Fe 3 O 4 @Au Composite Mnps On the Organsmentioning
confidence: 99%
“…On the other hand, thiol ligands such as 11-mercaptoundecanoic acid (MUA) could also introduce the groups such as a carboxyl terminal on its surface based on Au-S chemistry, and the bioconjugation could be carried out by covalent interaction between biomolecules and the carboxyl groups via EDC as a cross-linker. The modified GoldMag composite nanoparticles with or without crosslinkers are of great interest for magnetic bimolecular separation, 16,33 bio-sensors for molecular detection, 34,35 contrast agents 36,37 for MRI and magnetically targeted drug delivery. 38 Based on the Au-S specific bond of cysteine or methionine and gold nanoparticles assembled on magnetic particle surface, Okada's group created a variety of peptide tags containing methionine and cysteine and established a novel protein purification system using the "methionine tags."…”
Section: Modification and Applications Of Goldmag Composite Particlesmentioning
confidence: 99%
“…The process of forming gold nanoparticle shell on the core was followed using SEM (data not shown), and a two-step process was revealed. Gold seeds with 2-3 nm in diameter were firstly adsorbed on the surface that supplied numbers of small, randomly oriented crystalline domains for the following seed mediated growth of the Au particles (Zhou et al, 2010). Then the gold seeds began to grow under the reducing condition of sodium borohydride until a continuous shell was selectively formed.…”
Section: Sem Characterizationmentioning
confidence: 99%